2002
DOI: 10.1002/ajh.10080
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive growth of epithelial carcinomas following treatment with nucleoside analogues

Abstract: Two patients, one with B-cell chronic lymphocytic leukemia (CLL) and one with hairy-cell leukemia (HCL), were treated with immunosuppressive chemotherapy. The patient with CLL was a 54-year-old female, who had had a squamous cell carcinoma (SCC) excised from her forehead 5 months before receiving the ®rst course of¯udarabine. During thē udarabine treatment, the patient developed a local SCC relapse and metastases in the neck. The carcinoma was treated by excision and radiotherapy, and further¯udarabine treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…Fludarabine depletes CD3 þ , CD4 þ , and CD8 þ lymphocytes over a period of many months. 39,40 Larsen et al 41 reported metastatic SCC in one patient following treatment with fludarabine and in another after 2-CdA. Davidovitz et al 42 reported a patient with a flare of scalp SCC following treatment with fludarabine.…”
Section: Discussionmentioning
confidence: 99%
“…Fludarabine depletes CD3 þ , CD4 þ , and CD8 þ lymphocytes over a period of many months. 39,40 Larsen et al 41 reported metastatic SCC in one patient following treatment with fludarabine and in another after 2-CdA. Davidovitz et al 42 reported a patient with a flare of scalp SCC following treatment with fludarabine.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, an aggressive course of squamous cell carcinoma (SCC) with diffuse metastasis was noted after treatment with fludarabine. [ 42 ] The authors suggested that T cell depletion by fludarabine was responsible for the sudden transformation in the biological course and behavior of the SCC. Another study of cladribine and second cancers in patients with CLL did not demonstrate increase in risk of second malignancies in CLL except for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of cutaneous malignancies in CLL may be related to abnormal immune surveillance inherent to CLL itself, a relative photosensitivity of CLL patients, increased medical contact and thus earlier diagnosis, and/or an effect of immunosuppressive treatments commonly administered for CLL (Buschfort et al, 1997;Robak et al, 2004). This association is clinically relevant as both melanoma and NMSCs are not only more common, but also potentially more aggressive in CLL patients compared to the general population (Bridges & Steinberg, 1986;Hartley et al, 1996;Davidovitz et al, 1997;Larsen et al, 2002;Royle et al, 2011).…”
mentioning
confidence: 99%